Foreign investment in the petroleum and mineral industries : case studies of investor-host country relations - Mikesell, Raymond Frech; Bartsch, William H.; Resources for the Future (Baltimore : Published for Resources for the Future by Johns Hopkins Press, 1971)
The purpose of this book is to examine the relationships between foreign investors in petroleum and minerals and the governments of the host countries with a view to analyzing the problems which affect the production of resources. Also to ascertain the impact of foreign investment in resource industries on the economic and social development of the host countries.
Includes index
Includes bibliographical references.
usc 11/10/18
Loans
Keywords: Petroleum industry and trade; Mineral investment; Investments, Foreign; Host countries (Business)